The projective hinge: phylogeny and ontogeny for a new descriptive geometry - De Rosa, Agostino (DISEGNARECON, 2012)
The architect- draughtsman uses a theoretical–graphic code whose foundations - of obvious Platonic lineage - attempt to organize and make sense to the reality. Perhaps the most powerful tool that he has in his hands to translate the existing world in a dense and polysemous model and to envisage the future one, in a compelling and creative way, becomes from descriptive geometry. Today, the context in which the architect works is violently changed and the "geometry", in the digital image, seems to have lost memory of its projective origins. Two loci - one related to the stonecutting’s tradition, the other to the experiences of contemporary art - seem to be able to bring out in a renewed way, "the figures of the demonstration" associated with descriptive geometry.